Ex Vivo Comparison of the Biomechanical Properties of Hand‐Sewn and Stapled Jejunoileal Anastomoses in Horses. Issue 4 (11th April 2014) - Bracamonte, José L.; Anderson, Stacy L.; Hendrick, Steven; Barber, Spencer M.; Deutscher, David; Sumner, David
<x xml:space="preserve">Abstract</x> Objective To compare bursting strength, construction time, and anastomotic dimensions of 4 jejunoileal anastomotic techniques. Study Design Experimental ex vivo study. Animals Adult horses (n = 12). Methods Jejunoileal anastomoses were constructed from harvested ileal and distal jejunal segments using a single‐layer Lembert technique (1HS), double‐layer simple continuous/Cushing technique (2HS), stapled side‐to‐side technique (SS), or stapled functional end‐to‐end technique (FEE). Anastomotic construction time was recorded. Bursting pressures (BP), bursting wall tension (BWT), percentage of mean anastomotic luminal diameter reduction, percentage of luminal diameter reduction relative to adjacent ileal and jejunal diameters and stomal length, were calculated. Results FEE had the shortest construction time. BP of 1HS and 2HS was significantly higher than FEE and SS (P < .001), which were not different from each other (P = .67). There were no significant differences in BP (P = .25) and BWT (P = .21) between 1HS and 2HS. Mean luminal diameter reduction was less for 1HS (25.1%) than for 2HS (34.8%), however, not statistically different (P = .12). Luminal diameter reduction relative to ileal diameter was significantly less for 1HS (15.2%) than for 2HS (28.47%; P = .012). Luminal diameter reduction relative to jejunal diameter was less for 1HS (32.4%) than 2HS (44.6%) but not statistically different; P = .07). Stomal length was significantly larger for SS (9.93 cm) than FEE (7.32 cm; P = .0002). Conclusion 1HS and 2HS jejunoileal anastomosis are equal in strength; however, 1HS results in less relative luminal diameter reduction. SS and FEE have comparable strength but fail at significantly lower BPs than hand‐sewn jejunoileal anastomoses.